AN ASSESSMENT OF THE EFFECT OF THE ACTIVE AND PASSIVE POLITICAL BEHAVIOR OF CITIZENS ON GOVERNANCE AND DEVELOPMENT IN NIGERIA - LAMBE EMMANUEL OYEWOLE; HASSAN SEYID ISHOLA; BASHIR OLADIMEJI ABDULRAZAQ (International Studies Journal)
Democratic elections are fundamental to the functioning of democratic systems, providing citizens with the opportunity to participate in political decision-making processes. However, in third world countries, the extent and nature of political participation vary widely, influenced by a range of socio-economic, cultural, and institutional factors. This research aims to provide insights into the phenomenon of active and passive thinking in democratic elections, highlighting its implications for democratic governance and development. Using the quantitative and primary methods of research and the research drawing on a synthesis of existing literature and empirical studies, the research explores the factors influencing political participation and electoral behavior among citizens in these contexts. Socio-economic, cultural, institutional, and informational factors are analyzed to understand the prevalence of active and passive thinking in democratic elections, with implications for democratic governance and development outcomes. The research found out that, Nigeria democracy is unique to western democracy therefore results to varying outcomes. The research recommends that, INEC in collaboration with the National Assembly needs to reconfigure campaigns to ensure tribalism and identity are eliminated during elections. There is urgent need to foster inclusivity and social cohesion by addressing underlying socio-economic disparities and promoting equal opportunities for all citizens. Encourage participation of marginalized groups in decision-making processes and ensure their representation in political institutions.